Forrest Gump - Finerman, Wendy; Tisch, Steve; Starkey, Steve; Roth, Eric, 1945-; Zemeckis, Robert, 1952-; Hanks, Tom.; Wright, Robin, 1966-; Sinise, Gary.; Williamson, Mykelti; Field, Sally; Burgess, Don, 1956-; Schmidt, Arthur; et al. ([United States] : Paramount Home Entertainment, 2001)
The story follows the life of low I.Q. Forrest Gump (Tom Hanks) and his meeting with the love of his life Jenny. The film chronicles his accidental experiences with some of the most important people and events in America from the late 1950's through the 1970's including a meeting with Elvis Presley, JFK, Lyndon Johnson, Richard Nixon, fighting in Vietnam, etc. The problem is, he doesn't realize the significance of his actions. Forrest becomes representative of the baby boomer generation having walked through life blindly.
Information from pre-release promotional materials; release date: Aug. 28, 2001.
Originally produced as a motion picture in 1994.
Based on the novel by Winston Groom.
Special features: Forrest Gump commentary by director Robert Zemeckis, producer Steve Starkey, and production designer Rick Carter; Through the eyes of Forrest Gump, a making-of documentary (ca. 29 min.); The magic of makeup, a featurette on the aging techniques used in the film; Through the ears of Forrest Gump, a feature on the sound design of the film; Building the world of Forrest Gump, a feature on the production design of the film; Seing is believing: the visual effects of Forrest Gump; photo gallery; screen tests; theatrical trailer.
Director of photography, Don Burgess ; editor, Arthur Schmidt ; music, Alan Silvestri ; production designer, Rick Carter ; costume designer, Joanna Johnston.
Tom Hanks, Robin Wright, Gary Sinise, Mykelti Williamson, Sally Field.
Keywords: People with mental disabilities -- United States -- Drama; Young men -- United States -- Drama; Love -- Drama; Feature films; Video recordings; Feature films; Love; People with mental disabilities; Video recordings; Young men; United States; Comedy films; Films for the hearing impaired; Comedy films; Drama; Films -- for the hearing impaired